The Effectiveness Of Football Training Programs On Some Physiological Components Using The Inbody 230 - FEDLAOUI, HASNI; aamerna, MESSAOUDi (sports creativity, 2025)
This study aims to highlight the effectiveness of the training programs applied by some football coaches and determine their effects on some physiological components of the MC team players and by applying the experimental method to suit the nature of the study as well as the interview tool to explain the Inbody230 test method, to evaluate the following measurements: BW, MMS,P FM, to assess the importance that trainers attach to the planning process, the study was conducted on 27 senior players with an average of 24.00 years and an average BMI of 22.485 kg / M 2. As the players underwent the coach's program, he observed the effect of the program statistically significant increase in the total skeletal muscle mass from the initial value from 30,814 kg to 34,651 kg, an increase of 3,837 kg And the input value by 3.4% from the initial value from 15.19% to 11.97%.